Historical Ecology and Ethnobiology: Applied Research for Environmental Conservation and Social Justice - Armstrong, Chelsey Geralda; Veteto, James R. (Ethnobiology Letters, 2015)
Historical ecology provides a research program and toolkit for applied interdisciplinary research in ethnobiology. With a focus on long-term changes in built environments and cultural landscapes, historical ecology emphasizes the need for scientific collaboration between disciplines for more relevant and applied academic research—particularly in service to environmental conservation and social justice.